2016
DOI: 10.14256/jce.1182.2014
|View full text |Cite
|
Sign up to set email alerts
|

Arhitektonska i strukturna analiza povijesnih građevina

Abstract: Architectural and structural analysis of historical structuresHistorical structures are integral to the cultural heritage of the world and ought to be safely preserved for posterity. An interdisciplinary approach is critical in the conservation and restoration of masonry structures. Taking this into consideration, this study discusses Gok Madrasah, a 750 year-old structure situated in Amasya, Turkey, in terms of art history and structural engineering. An analysis of decorative elements is made in the paper fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The lateral deformations and tensions at these locations necessitate the use of iron braces. It is safe to state that the architects of the Ottoman architecture were aware of this and took the necessary precautions (Çakır and Koçyiğit, 2016). The dynamic analyses indicated that the main domes, the narthex, and the minarets, all of which are involved in the movement of the building, could be damaged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral deformations and tensions at these locations necessitate the use of iron braces. It is safe to state that the architects of the Ottoman architecture were aware of this and took the necessary precautions (Çakır and Koçyiğit, 2016). The dynamic analyses indicated that the main domes, the narthex, and the minarets, all of which are involved in the movement of the building, could be damaged.…”
Section: Discussionmentioning
confidence: 99%
“…The main mass, narthex, minarets, and arches, were built using face stones, while the domes were built with bricks from Khorasan. The physical and mechanical properties identified in the laboratory tests performed on the materials that were used in another work in the same city were assigned to these parts (Çakır and Koçyiğit, 2016). The physical and mechanical properties of these materials are presented in Table 1.…”
Section: Finite Element Model and Materials Propertiesmentioning
confidence: 99%
“…It is difficult to identify this problem by traditional calculations, using for instance approximate graphical methods, and by selecting usual relationships between structural elements [8] or the compression-tension analogy, simply because the displacements are very small. On the other hand, global structural models that are most often used in modern numerical calculations [9] cannot adequately cover complex behaviour of small details, especially in the post-critical region (where many specific data are required). Furthermore, common experimental tests, involving determination of axial force levels in columns of historic buildings, are normally not conducted in the vicinity of contacts, and may lead researchers to totally wrong conclusions, as stress concentrations are already distributed (Figure 2.d).…”
Section: Introductionmentioning
confidence: 99%